انتشار اضطراب الوظيفة الدرقية عند مرضى الداء السكري من النمط الثاني - سلمان, ربا; بوبو, أريج; رحال, يوسف (Latakia University Journal -Medical Sciences Series, 2017)
المقدمة: يعتبر الداء السكري نمط2 والاضطرابات الدرقية من أشيع الأمراض الغدية المشاهدة في الممارسة السريرية. تؤثر الاضطرابات الدرقية بشكل واسع على الاستقلاب وتشكل عامل خطورة للأمراض القلبية الوعائية. إن هدف هذه الدراسة هو تقييم انتشار اضطراب الوظيفة الدرقية عند مرضى الداء السكري نمط2.الهدف: دراسة نسبة انتشار ونمط توزع الاضطرابات الدرقية عند مرضى الداء السكري نمط2.الطرائق والوسائل: شملت الدراسة 362 شخص (204 مريض مصاب بالداء السكري نمط2 و158 شخص غير سكري), أجري الـTSH لمجموعة السكريين ومجموعة الشاهد كإختبار مسح من أجل تقييم الوظيفة الدرقية وكذلك تم إجراء FT4 عندما تكون قيم الـTSH مضطربة من أجل تحديد نوع الاضطراب. تم دراسة ارتباط انتشار الاضطرابات الدرقية عند المرضى السكريين نمط2 مع عدة عوامل شملت: الجنس, العمر, مدة الاصابة, مشعر كتلة الجسم, نوع المعالجة، المستويات المصلية لسكر الدم الصيامي والشحوم الثلاثية والكولسترول.النتائج: بلغت نسبة انتشار الاضطرابات الدرقية عند مجموعة السكريين من النمط الثاني13,2% وعند مجموعة الشاهد6,3% (p=0,031 أقل من 0,05 فهي فروق ذات دلالة احصائية هامة). وكان الاضطراب الدرقي الاكثر شيوعا" عند السكريين من النمط2 هو قصور الدرق تحت السريري بنسبة 8,3%. وتبين أن الاضطرابات الدرقية عند السكريين من النمط2 ترتبط بعلاقة هامة احصائيا" بعدة عوامل شملت: الجنس (الإناث > الذكور), العمر>60سنة, المعالجة بالأنسولين, سكر دم صيامي > 130ملغ/ دل, شحوم ثلاثية > 150ملغ/ دل.التوصية: إجراء مسح للوظيفة الدرقية عند كل المرضى المصابين بالداء السكري نمط2.Background: Diabetes mellitus type2 (T2DM) and thyroid dysfunction (TD) are the two most common endocrine disorders in clinical practice. The unrecognized TD may adversely affect the metabolic control and add more risk to an already predisposing scenario for cardiovascular diseases. The objective of this study was to investigate the prevalence of TD in patients with type2 diabetes mellitus.Objective: To determine the prevalence and patterns of thyroid dysfunction in patients with type2 diabetes mellitus.Material and methods: Study included total 362 subjects (204 type2 diabetic patients and 158 healthy non diabetic subjects). Agroup of type2 diabetic patients and control group were evaluated for thyroid dysfunction by testing TSH and FT4 when TSH was abnormal. The correlation of prevalence of thyroid disorder with gender distribution, age distribution, duration of diabetes, BMI, treatment, fasting plasma glucose (FPG), serum triglyceride and serum cholesterol was then done in diabetic patients. The observations and interpretations were recorded and results obtained were statistically analyzed.Results: The prevalence of thyroid dysfunction among type2 diabetic patients was found to be 13,2%. In the control group, the prevalence of thyroid dysfunction was 6,3%. There was a significant difference between diabetics and control subjects p= 0,031.The most frequently TD in type2 diabetic patients was subclinical hypothyroidism (8,3%). Thyroid dysfunction was significantly correlated with gender (women > man), age < 60 years, FPG > 130mg/dl, TG > 150mg/dl and insulin treatment in type2 diabetic patients.Conclusion: Screening of thyroid dysfunction shoud be done in all Type2 diabetic patients.